(3eSFhdjI UGMH GdYed HVeGf SdGeI GdYeGd h JCejf HjFI GdYed habG dCMcGe GdbGfhf GdeUQi (B/ s - (3TQja eMeO fhQ GdOjf YHOGdaJGMs; (3CMeO MSf GdHQYi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JfGhdJ GdOQGSI GdJRGe UGMH GdYed HVeGf SdGeI GdYeGd h HjfJ fTCJg h eagheg h TQhWg h eMdg h CSGSg GdbGfhfi(B: (3ceG fGbTJ gPG GdGdJRGe ai VhA CMcGe bGfhf GdJCejfGJ GdELJeGYjI Qbe (B79 (3dSfI (B1975 (3h bGfhf GdYed Qbe (B12 (3dSfI (B2003. (3h CXgQJ GdJRGeGJ UGMH GdYed HGJNGP ELQGAGJ JCejf HjFI GdYed h GfTGA dLGf GdSdGeI h GdUMI GdegfjI(B: (3h CTGQJ Edi Mb GdYGed ai GdGfSMGH ef hVY GdYed GdNWQ(B. (3ceG HjfJ OhQ GdCLgRI GdeYfjI ai EUOGQ GdJQGNjU GddGReI dEbGeI GdefTBJ h cPdc GdeYfjI HeQGbHI JfajP UGMH GdYed GdJRGeg(B. (3hCHQRJ(B: (3cPdc(B: (3GdeSFhdjI GdeOfjI dUGMH GdYed GdbGFeI Ydi CSGS GdNWC hGLH GdEKHGJ(B: (3hcPdc eSFhdjJg Yf CYeGd JGHYjg(B: (3ceG fGbTJ eSFhdjJg GdLfGFjI h HjfJ CQcGf eNGdaJg CMcGe GdSdGeI cGdUMI GdegfjI h JCejf HjFI GdYed GdebQQI bGfhfG h GdYbhHGJ GdLfGFjI GdebQQI Ydi eNGdaJgG h GdJOGHjQ GdGMJQGRjI GdefXeI dVeGf SdGeI GdYeGds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdELJeGYjI (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B342-355s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3JTQjYGJ ELJeGYjIs; (3GdbGfhf GdeUQi s; (3SdGeI GdYeGd h JCejf HjFI GdYed s; (3eSFhdjI UGMH GdYed s; (3GdJaJjT GdOhQjs; (3JhajQ GdJZPjI GdefGSHIs; (3GdeNGWQ GdajRjGFjIs; (3GdeNGWQ GdHjhdhLjgs; (3GdeNGWQ GdcjejGFjIs; (3GdeNGWQ GdSdHjIs; (3GdJOGHjQ GdGMJQGRjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3JTQjYGJ ELJeGYjIs